2015
DOI: 10.4236/jdm.2015.54039
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Medication Beliefs & Adherence to Medication among Diabetic Patients Attending the Diabetic Clinic in a Teaching Hospital in Southwest Nigeria

Abstract: Background: Non-adherence to drug therapy is an important cause of treatment failure among patients with chronic conditions like diabetes. Previous researches have presented associations among personality traits, medication beliefs and adherence to long-term medication treatment in individuals with different chronic diseases. However, there is limited knowledge about associations among personality traits, medication belief and adherence to diabetic treatment in Africa. It was on this basis that this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…Moreover, no association to HbA1c was found. Analogous to our results, in a study done in Nigeria in 2015, demographic data showed that only sex had a signi cant relationship with medication adherence, and no signi cant association was found among other factors [47].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, no association to HbA1c was found. Analogous to our results, in a study done in Nigeria in 2015, demographic data showed that only sex had a signi cant relationship with medication adherence, and no signi cant association was found among other factors [47].…”
Section: Discussionsupporting
confidence: 86%
“…Além disso, estiveram todos de acordo com o que a literatura vem afirmando, sobre os fatores mais adaptativos da personalidade estarem relacionados ao comportamento de adesão e enfrentamento das doenças crônicas (Christensen et al, 2002;Axelsson et. al., 2011;Adeniran et al, 2015;Costa et al, 2018).…”
Section: Discussionunclassified
“…Já o estudo de Adeniran et al (2015) com pacientes portadores de Diabetes Mellitus, constatou que os traços de personalidade podem influenciar a adesão ao tratamento, e principalmente aqueles com alta pontuação no fator Neuroticismo, que demonstram dificuldades em aderir aos recursos terapêuticos. Na mesma direção, Axelsson, Brink, Lundgren e Lötvall (2011) verificaram que em pacientes com doença crônica a baixa adesão também estava relacionada com uma maior pontuação em Neuroticismo e menor em Realização.…”
Section: Introductionunclassified
“…Illness related factors like side effects of medications, beliefs about the illness, treatments complexity and lack of insight are barriers to medication adherence (11). The beliefs about medication which influence non adherence are moderated by specific personality traits (12). Personality trait can predict healthcare utilization as well as health outcomes (13).In Italy neuroticism and conscientiousness were the most personality traits associated with psychotropic medication non adherence.…”
Section: Introductionmentioning
confidence: 99%